Inventory lists of library collections as a source for the history of books, with special focus on the collection of Nikola Pavlov Gundulić from 1469 (Libellarium: journal for research in the field of information and related sciences, 2009)
The inventory lists of private library collections may be counted among the most significant sources for the study of the history of books in the Middle Ages and the Renaissance. These inventories provide a true picture of the reading material used in a given historical period and reveal their owners’ spiritual preoccupations as well as those of their contemporaries. Many books listed in the inventories had disappeared from the collections over time, so the inventories remain the sole indicators helping us to reconstruct the spiritual life of the different social environments. The inventories deserve to be treated with exceptional reverence by the book historians.Example used by the author to show the type of information that might be learned from the inventory of a private library is the inventory of books that Nikola Pavlov de Gondola of Dubrovnik gave as a gift, in 1469, to the Benedictine monastery of St. Mary’s on the island of Lokrum near Dubrovnik. The inventory list comprises sixteen titles; among them are two milestones, Boccaccio’s The Decameron and Genealogies of the Gentile Gods. The two are the oldest specimens of these books ever to be discovered in Croatia. Using the standard methodology for book inventory analysis, developed by the so-called ‘middle generation’ of book historians, the author first establishes which book the inventory entry refers to and, then, he supplies information on the book. Finally, for the most important books, he sketches for the reader a wider context of the book ownership and use. The author also stresses the importance of the numerous private library inventories kept in the archives of Dubrovnik, Split, Zadar, etc. He argues that the publication and an in-depth analysis of the surviving inventories would supply valuable information not only on the books bought and read by their owners but also on the intellectual and cultural preoccupations of the social environments (towns) in which the owners lived.
Keywords: Nikola Pavlov de Gondola; library inventories; Dubrovnik libraries; monastery libraries; Dubrovnik